Rancang Bangun Aplikasi Kamus Korea-Indonesia Menggunakan Metode Binary Search Berbasis Android - Anggraeni, Anindhia; sukmaaji, anjik; Sutanto, Teguh (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Along with the rapid advancement of South Korea today, resulting in increased interest in the people of Indonesia to study in South Korea. One example is based on an excerpt from the article website KBRISeoul, of 70 students from Indonesia in 2004 to about 1200 students until January 2015. The basic requirement is needed when going to live in another country is a dictionary.Increasing number of users and the android operating system is open source can be used to create an Indonesian-Korean dictionary applications. Existing dictionary on android is currently still no way read hangul letters, then in the Indonesian-Korean dictionary applications that will be made there way read hangul letters and how search is offline which is expected to facilitate the users in finding the information word at any time and wherever. The methodology of research in Indonesia-Korean dictionary is using Binary Search. The advantage to using a binary search is with a data dictionary that many will be easier to look and fast search terms found.With the Indonesian-Korean dictionary applications based on Android will be able to assist the user in the search process said Indonesia and Korea said whenever and wherever